2022
DOI: 10.15586/aei.v50i2.491
|View full text |Cite
|
Sign up to set email alerts
|

Three-year pollen and fungi calendar in a Mediterranean region of the Northeast Greece

Abstract: Introduction and objectives: Pollen calendars have been proved clinically important in allergic disease management, as differences in airborne allergens exist not only between different countries but also between regions of the same country as well. This study aims to provide new data regarding the atmospheric pollen and fungi content of a Mediterranean region (Western Thrace/North-East Greece) and discuss seasonal trends, differences in pollen grains and fungi spores’ circulation over the years, and correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Comparable annual distribution patterns were observed in other studies, carried out at similar latitudes in Europe to Leicester (Corden and Millington, 2001; Martínez-Bracero et al, 2022; Nikkels et al, 1996; Sadys et al, 2016a). However, at locations with a more southerly latitude and Mediterranean climate these spores tended to appear earlier in the year and remain for a longer period of time (Anees-Hill et al, 2022; Antón et al, 2019; Katotomichelakis et al, 2016; Katsimpris et al, 2022; Reyes et al, 2016; Sousa et al, 2016). Of the more abundant spores observed in this study only Leptosphaeria showed a differing annual distribution compared to other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable annual distribution patterns were observed in other studies, carried out at similar latitudes in Europe to Leicester (Corden and Millington, 2001; Martínez-Bracero et al, 2022; Nikkels et al, 1996; Sadys et al, 2016a). However, at locations with a more southerly latitude and Mediterranean climate these spores tended to appear earlier in the year and remain for a longer period of time (Anees-Hill et al, 2022; Antón et al, 2019; Katotomichelakis et al, 2016; Katsimpris et al, 2022; Reyes et al, 2016; Sousa et al, 2016). Of the more abundant spores observed in this study only Leptosphaeria showed a differing annual distribution compared to other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cladosporium (66%), Alternaria (1.67%) and Leptosphaeria (1.21%) dominated in Szczecin in Poland (Bednarz & Pawłowska, 2016). Cladosporium spores were noted as a primary airborne fungal component in both indoor and outdoor environments in Netherlands (Segers et al, 2023), Lithuania (Sauliene et al, 2023) and North-East Greece (Katsimpris et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Western Thrace shows that the main spore season for fungal circulation in the atmosphere was observed from May to November. The highest concentration of Alternaria and Cladosporium was noticed in summer, with its peak in June for Alternaria and in July for Cladosporium [37].…”
Section: Living Environment Of Fungimentioning
confidence: 94%
“…However, Alternaria and Cladosporium generally peak in midafternoon during periods of low humidity [8,39]. They are positively correlated with the daily average temperature and negatively correlated with the relative humidity [13,37].…”
Section: Living Environment Of Fungimentioning
confidence: 99%